1998
DOI: 10.1063/1.120882
|View full text |Cite
|
Sign up to set email alerts
|

Regular step arrays on silicon

Abstract: Highly regular arrays of steps are produced on vicinal Si͑111͒7ϫ7. The step edges are atomically straight for up to 2ϫ10 4 lattice sites. The terraces are single domain, which produces a minimum kink width of 2.3 nm ͑half a 7ϫ7 unit cell͒ and thus a high barrier for creating kinks. Criteria for obtaining optimum step arrays are established, such as the miscut ͓Ϸ1°towards ͑112͔͒ and an annealing sequence which passes through step bunching regions quickly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 23 publications
(11 reference statements)
1
95
0
Order By: Relevance
“…Stepped Si͑111͒ templates have been prepared with high perfection by appropriate annealing sequences. [29][30][31] At low enough coverage there is only a single gold chain in the unit cell of such vicinal surfaces, while the flat Si(111)5 ϫ2-Au structure consists of two Au chains per unit cell. 32 Figure 1 shows how vicinal Si͑111͒ surfaces containing the stable ͓1 1 0͔ steps can be classified into two groups, one tilted with its normal towards the ͓1 1 2 ͔ azimuth with one broken bond at the step edge, the other towards ͓1 1 2͔ with two broken bonds.…”
Section: Structure Of Gold Chains On Stepped Si"111…mentioning
confidence: 99%
See 2 more Smart Citations
“…Stepped Si͑111͒ templates have been prepared with high perfection by appropriate annealing sequences. [29][30][31] At low enough coverage there is only a single gold chain in the unit cell of such vicinal surfaces, while the flat Si(111)5 ϫ2-Au structure consists of two Au chains per unit cell. 32 Figure 1 shows how vicinal Si͑111͒ surfaces containing the stable ͓1 1 0͔ steps can be classified into two groups, one tilted with its normal towards the ͓1 1 2 ͔ azimuth with one broken bond at the step edge, the other towards ͓1 1 2͔ with two broken bonds.…”
Section: Structure Of Gold Chains On Stepped Si"111…mentioning
confidence: 99%
“…Interestingly, the Si(111)5ϫ2-Au surface appears to be stabilized by a lattice gas of additional Si atoms that provide the energetically optimal band filling. 31,38 Thus autodoping by built-in defects might be a common phenomenon in these chain structures.…”
Section: Band Fillingmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Himpsel and co-workers have experimentally demonstrated that vicinal Si͑111͒ surfaces can serve as templates for self-assembly of one-dimensional ͑1D͒ nanostructures, 17,18 because a regular array of straight steps can be obtained on these surfaces. [19][20][21] Improving their method of the straight-step preparation by substrate annealing with step-parallel direct current ͑dc͒, we have found that the "kink-up" direction ͑ascending kinks of the steps͒ of the dc is effective to obtain atomically straight step edges ͑on the order of 1 m in length͒ probably due to electromigration of the surface atoms. 22 We have studied the growth behavior of Si ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 On the other hand, self-assembly of one-dimensional ͑1D͒ nanostructures such as of Au and CaF 2 has been demonstrated 16,17 by using regular step arrays on vicinal Si͑111͒ surfaces. [18][19][20] In this letter, we study self-assembly of Ge on such highly ordered step substrate of Si͑111͒-7 ϫ 7. Scanning tunneling microscopy ͑STM͒ reveals the growth mechanism of 1D arrays of Ge nanoclusters along the step edges.…”
mentioning
confidence: 99%